Paradoks Kebijakan Mutu Pesantren: Studi Kasus Implementasi Standar Mutu Pendidikan Nonformal Yayasan Al-Jamil - Bambang Dwi Wijayanto (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2026)
Abstract Strengthening the quality of pesantren education is an important part of human resource development toward Indonesia Emas 2045. This study aims to analyze the implementation gap of the 2024 Quality Standards for Nonformal Pesantren Education at Yayasan Al-Jamil and its implications for human resource development. A qualitative approach with a single-case study design was employed at three Yayasan Al-Jamil locations in East Kalimantan, South Jakarta, and Yogyakarta. Data were collected through in-depth interviews, participatory observation, and documentation. The findings show that the foundation demonstrates strength in curriculum and learning processes, yet still faces limitations in institutional and financing aspects. These findings indicate a pesantren quality policy paradox, namely normative recognition that is not fully followed by adequate material support. Therefore, more inclusive, adaptive, and output-based funding policies are needed for self-funded pesantren. Keywords: pesantren quality; nonformal Islamic education; policy implementation; self-funded pesantren; human resources.